Gender-Dependent Association of Vitamin D Deficiency with Obesity and Hypercholesterolemia (LDLC) in Adults - Almesri, Norah; Das, Nagalla S.; Ali, Muhallab E.; Gumaa, Khalid; Giha, Hayder A. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Background: Obesity, dyslipidemia and vitamin D deficiency are growing health problems in the Arabian Gulf region. Their association with each other is yet to be clarified. Methods: Three-hundred and fourteen Bahraini adults, 164 males and 150 females comparable in median age (34.5 vs. 31.0 yrs), body mass index (BMI), and ethnicity were recruited. The plasma level of 25-hydroxyvitamin D3 (25OHD3) was measured by chemiluminescent immunoassay and lipid profile parameters were measured by an automated clinical chemistry analyzer. Based on BMI, study subjects were grouped into underweight, normal, overweight, moderate obesity, and severe obesity subjects. Results: The results revealed an extremely high prevalence of vitamin D deficiency (79.9%) and insufficiency (18.8%). The predictors of low 25OHD3 levels were female gender, small age, conservative dressing, least exposure to sunlight, and less fish intake. In all subjects, the lowest 25OHD3 level was seen in underweight and severe obesity groups. Furthermore, the 25OHD3 level was significantly higher in males as compared to females and it was positively correlated with the age. However, detailed analysis showed that overweight males unlike females had the highest 25OHD3 levels which were significantly higher than in the severely obese males. While the lipid profile parameters were positively correlated with BMI, the total and LDL cholesterols were negatively correlated with the levels of 25OHD3 in males. Conclusion: Vitamin D deficiency was associated with both severely obese and underweight subjects, in the former it was likely to be institutional while in the latter it was likely to be nutritional. Furthermore, hypercholesterolemia (LDL-C) was associated with 25OHD3 sub-normality. Further analysis revealed that the significant associations were gender-dependent.
Keywords: BMI